Adjectival Phrases In Javanese: Internal Functions - Surana, Surana; Dwi Untari, Tunjung; Pairin , Udjang; Adipitoyo, Sugeng; Wijoyanto, Danang; Rizky Wahyudi, Ahmad (Proceeding of International Joint Conference on UNESA, 2025)
This study investigates the internal syntactic structure of adjectival phrases in Javanese, focusing on head-modifier relationships and constituent configurations—a topic that remains underexplored in both Javanese linguistics and syntactic theory. Employing a descriptive qualitative approach grounded in Aarts and Aarts’ syntactic framework, the study analyzed 14 naturally occurring utterances and several written sources from Sidoharjo District, Sragen Regency, Central Java. Data collection involved participant observation, semi-structured interviews, and document analysis, while Immediate Constituent Analysis was used to examine the internal composition of each phrase. The findings reveal that Javanese adjectival phrases consistently position the adjective as the head and allow a diverse range of modifiers—including adverbs, nouns, verbs, pronouns, numerals, and adjectives—either before or after the head. These phrases exhibit both endocentric and exocentric patterns and frequently feature discontinuous or stacked modification structures. Such internal flexibility highlights the morphosyntactic richness of Javanese and challenges traditional models of phrase structure. The study contributes both to the descriptive grammar of Javanese and to broader typological perspectives on syntactic organization in morphologically complex languages.